Parameter-free solution of the Bohr Hamiltonian for actinides in the octupole mode - Lenis, D.; Bonatsos, D. (HNPS Advances in Nuclear Physics, 2020)
An analytic, parameter-free (up to overall scale factors) solution of the Bohr Hamil- tonian involving axially symmetric quadrupole and octupole deformations, as well as an infinite well potential, is obtained, after separating variables in a way reminiscent of the Variable Moment of Inertia (VMI) concept. Normalized spectra and B(EL) ratios are found to agree with experimental data for 226Ra and 226Th, the nuclei known to lie closest to the border between octupole deformation and octupole vibrations in the light actinide region